ECUMENISM AS A FACTOR IN THE DEVELOPMENT OF INTERCONFESSIONAL PROCESSES (The Journal of Interdisciplinary Human Studies, 2026)
The article examines the phenomenon of ecumenism as a dynamicreality that has evolved from the idea of church unity into a contemporary model ofinterconfessional and interreligious interaction. The study analyzes the historical andtheological premises for the emergence of the ecumenical movement and highlights theimpact of social, cultural, and political factors on its development in the twentieth andtwenty-first centuries. Particular attention is paid to the processes of institutionalizationof ecumenism, its transformation into a stable form of religious cooperation, and theadaptation of universal principles of Christian dialogue to specific regional traditions.The article emphasizes the significance of ecumenism as a factor in strengthening aculture of religious tolerance, civil peace, and spiritual solidarity in contemporarysociety.
Keywords: ecumenism; interreligious dialogue; confessional relations; Christianity; ecumenical movement; World Council of Churches; religious tolerance